Influence of adiponectin gene variants and plasma fatty acids on systemic inflammation state association–A cross‐sectional population‐based study, São Paulo, Brazil. Issue 2 (20th October 2015) - Maintinguer Norde, Marina; Oki, Érica; de Castro, Inar Alves; Pacheco Souza, José Maria; Teixeira Damasceno, Nágila Raquel; Mara Fisberg, Regina; Lobo Marchioni, Dirce Maria; Macedo Rogero, Marcelo
Abstract : Scope: Interactions between adiponectin genetic variants and plasma fatty acid profile can modulate plasma inflammatory biomarker concentration and the risk for metabolic diseases. The aim of this study was to investigate the interaction between single nucleotide polymorphisms of the adiponectin gene and plasma fatty acid profile in modulating the odds for systemic inflammation in a cross‐sectional population‐based study. Methods and results: Inflammatory patterns comprised 11 inflammatory biomarkers. Among participants of the Health Survey of São Paulo, 262 adults (19–59 years) met the inclusion criteria. Anthropometric parameters, blood pressure, plasma inflammatory biomarker concentration, and fatty acid profile were measured and five single nucleotide polymorphisms of the adiponectin gene ( rs2241766, rs1501299, rs16861209, rs17300539, and rs266729 ) genotyped. Individuals in the upper 50th percentile for plasma araquidonic acid, n‐3 highly unsaturated fatty acid and estimated delta‐5‐desaturase activity, had reduced odds of being in the inflammatory cluster (OR (95% CI) = 0.55 (0.32–0.95), 0.50 (0.28–0.88) and 0.48 (0.28–0.83), respectively). Gene‐plasma fatty acid profile interaction was found between rs2241766 and n‐3 ( p = 0.019), rs16861209 and araquidonic acid and docosapentaenoic acid ( p = 0.044, p = 0.037, respectively), and rs17300539 and saturated fatty acid ( p = 0.019). Conclusion: Plasma fatty acid profile can interact with adiponectin gene variants to modulate the risk for systemic inflammatory state.